2009
DOI: 10.1080/19386380903405124
|View full text |Cite
|
Sign up to set email alerts
|

Metadata for Special Collections in CONTENTdm: How to Improve Interoperability of Unique Fields Through OAI-PMH

Abstract: Collection curators develop locally defined unique fields to support local requirements. As per the guidelines of the Open Archives Initiative Protocol for Metadata Harvesting (OAI-PMH), Simple DublinCore is the minimum requirement for exposing metadata to aggregators. Oftentimes the level of specificity of unique local fields is not translated well to Dublin Core, which may hinder the interoperability of the item metadata record. This paper researched 21 digital collections that were hosted in CONTENTdm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This research focuses on descriptive metadata as they are the foundation that enables users to find, identify and access digital objects within a system and across different platforms (Corrado and Moulaison Sandy, 2017). This research also acknowledges that no single descriptive metadata standard can work for all digital collections (Han et al, 2009). We also acknowledge that standardisation by nature is linked to a concept of universal representation, a Western framework for managing collections.…”
Section: Assumptions and Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…This research focuses on descriptive metadata as they are the foundation that enables users to find, identify and access digital objects within a system and across different platforms (Corrado and Moulaison Sandy, 2017). This research also acknowledges that no single descriptive metadata standard can work for all digital collections (Han et al, 2009). We also acknowledge that standardisation by nature is linked to a concept of universal representation, a Western framework for managing collections.…”
Section: Assumptions and Limitationsmentioning
confidence: 84%
“…Shareable metadata is commonly cited as an enabler for the wide sharing of documentary heritage collections. However, as pointed out by Han et al (2009), research addressing how curators adapt or customise metadata standards for a local setting or the degree to which this impedes interoperability remain scant. A decade later, this remains the case.…”
Section: Motivation For Studymentioning
confidence: 99%
“…Currently, there are initiatives such as the Open Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) and linked open data (LOD). In the case of OAI-PMH, this type of metadata permits maintaining the context as much as possible when metadata are shared with others (Han et al 2009); this also supports interoperability by combining them with other standard metadata such as encoded archival description (EAD). LOD provides links to outside resources and maps metadata to linked data with friendly vocabulary such as the RDF vocabulary (Disambiguating descriptions 2016).…”
Section: The Inclusion Of Datasets In a Special Collectionmentioning
confidence: 99%
“…Hutt & Riley's (2005) analysis found that date values were divided between those describing physical resources and digitized copie. Han, et al (2009) found that one third of ContentDM repositories included information about both physical and digital manifestations.…”
Section: Introductionmentioning
confidence: 99%